Probing Intermolecular Interactions in Binary Liquid Mixtures Using Femtosecond Laser-Induced Self-Defocusing. Issue 10 (October 2016) - Maurya, Sandeep Kumar; Das, Dhiman; Goswami, Debabrata
Photothermal behavior of binary liquid mixtures has been studied using a high repetition rate (HRR) Z-scan technique with femtosecond laser pulses. Changes in the peak–valley difference in transmittance (ΔTP–V ) for closed aperture Z-scan experiments are indicative of thermal effects induced by HRR femtosecond laser pulses. We show such indicative results can have a far-reaching impact on molecular properties and intermolecular interactions in binary liquid mixtures. Spectroscopic parameters derived from this experimental technique show that the combined effect of physical and molecular properties of the constituent binary liquids can be related to the components of the binary liquid.